Social and economical aspects of Miombo woodland management in Southern Africa: options and opportunities for research - Dewees, P. A. (1994)
Five themes are identified for social, economic and policy research relating to miombo woodland management in southern Africa. They are: (1) patterns of local institutional change; (2) household use of woodland products; (3) markets for woodland products; (4) longer term dimensions to woodland use and exploitation and (5) policy and legislation. These themes are by no means definitive or exhaustive, but are described here as a means of focusing on the scope of future research, and as a basis for identifying priorities.